The bookplates of the fund of Lituanica of the 18th century at the library of Lithuanian academy of science - Braziūnienė, Alma (Knygotyra, 2024)
This article is the sequel to the article "The Bookplates of the Fund of Lituanica of the 17th Century at the Library of Lithuanian Academy of Science."There are 6,524 books with 1,883 bookplates in the Fund of Lituanica of the 18th century. All of them were registered in the bookplates card index while recataloguing the fund.The first large group of all bookplates comprises manuscript inscriptions (provenancial, memorial, and dedicational). There are 613 of them. Provenancial ones make up 90% of all inscriptions. Those of monastery libraries make up only 10% of all inscriptions. This is different from the 17th-century books, where monastery inscriptions used to predominate.The second large group of bookplates consists of ex-librises, superex-librises, and book stamps. There are 1,267 of them, which is twice as many as manuscript inscriptions. It's natural because every inscription is unique, while bookplates of the second group can be easily multiplied.After reviewing all the 18th-century bookplates of Lituanica, the formation of this fund becomes clear. It was completed by mechanically selecting books published in the 18th century. Any larger private or library collections are not dominant. Inscriptions of solitary persons make up the majority in this fund.This review of bookplates is material that will help in studies of book history and especially in studying the history of libraries of Lithuania, their dispersion, and the history of book travel.
Keywords: -